ZEN and the Art of Teaching Systems Development - Greenbaum, Joan; Mathiassen, Lars (DAIMI Report Series, 1987)
There has been a great deal written about curriculum for teaching systems development, but very little said about the methods and practices of the teaching process itself. This article, in the form of an open letter to colleagues, addresses itself to the problems and experiences we have had in teaching systems development. Specifically, it focuses on the contradiction between education and experience and suggests some metaphors and methods for better integrating experience into the learning process.